2020
DOI: 10.1111/ajco.13430
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of and preference for disease prognosis and participation in treatment decisions among advanced cancer patients in Myanmar: Results from the APPROACH study

Abstract: Aim To investigate prognostic awareness, preference for prognostic information, and perceived and preferred roles in decision making among patients with advanced cancer in Myanmar. Methods A cross‐sectional survey was administered at the Yangon General Hospital to stage 4 cancer patients who were at least 21 years old and aware of their cancer diagnosis. Patients were asked questions about their prognosis, participation in treatment decisions, sociodemographic and clinical information. Data from 131 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Not knowing prognosis may be essential for patients as it allows hope [15,16,[27][28][29][30][31]. Other patients may avoid prognostic estimates out of fear that these evoke negative emotions or become reality [14,[32][33][34][35][36]. Some patients find prognosis too uncertain and therefore useless [9], or feel relieved when not having to understand medical information [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not knowing prognosis may be essential for patients as it allows hope [15,16,[27][28][29][30][31]. Other patients may avoid prognostic estimates out of fear that these evoke negative emotions or become reality [14,[32][33][34][35][36]. Some patients find prognosis too uncertain and therefore useless [9], or feel relieved when not having to understand medical information [37].…”
Section: Introductionmentioning
confidence: 99%
“…Still, relations between patients' prognostic information preference and personal characteristics remain understudied. Besides, while some studies reported associations with older age, female sex and lower income, research investigating the background and clinical characteristics of patients who reject prognosis is scarce [32,34,[41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the multisite APPROACH protocol, we aimed to recruit a sample of 200 participants. 20 , 21 To obtain this sample size, 473 patients were assessed for eligibility via daily screening of medical records of outpatients seen at the medical oncology and palliative care departments and inpatient medical and surgical wards and referrals from nurses and patient. Of the pool of patients, 266 were deemed ineligible based on medical record review or after being approached for the study or declined to participate.…”
Section: Research Methods and Designmentioning
confidence: 99%
“…We also assessed the relationship between prognostic awareness and preference for prognostic information and patient factors. Based on prior literature, we hypothesised that greater prognostic awareness and preference for receiving prognostic information would be associated with younger age, 13 , 16 higher education, 14 , 15 higher income 16 , 17 and higher symptom burden. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…In the absence of specific and validated instruments for evaluating patients' preference for receiving information about their prognosis and whether they want to be informed, we developed a draft questionnaire based on data from previous studies and discussion among the authors of this study (16)(17)(18)(19). The face validity of the draft questionnaires was confirmed by five patients in October 2021, and the questionnaires were revised by researchers.…”
Section: Questionnairesmentioning
confidence: 99%